A novel CFD-based computed index of microcirculatory resistance (IMR) derived from coronary angiography to assess coronary microcirculation. (June 2022) - Jiang, Jun; Li, Chenguang; Hu, Yumeng; Li, Changling; He, Jingsong; Leng, Xiaochang; Xiang, Jianping; Ge, Junbo; Wang, Jian'an
Hightlights: AccuIMR is a novel pressure-wire free approach to assess coronary microvascular disease. AccuIMR has excellent diagnostic performance in predicting wire-based IMR. AccuIMR is computationally efficient and only needs a few minutes for computation. Abstract: Objectives: This study sought to present a novel approach for computation of the index of microcirculatory resistance (IMR) and to evaluate its diagnostic performance. Background: IMR is a quantitative assessment to identify coronary microvascular dysfunction. However, its clinical use remains extremely limited. Calculation of IMR from coronary angiography images may increase the utility of coronary microvasculature assessment. Methods: 203 patients with 203 vessels were included in this study. Physiology measurements were obtained with pressure-wire in the whole cohort. The computational fluid dynamics (CFD)-based AccuIMR was computed and evaluated in a blinded fashion using wire-based IMR as the reference standard. Results: The overall diagnostic accuracy, sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) of AccuIMR for detecting coronary microvascular disease were 91.1% (95% CI: 86.4% to 94.7%), 89.4% (95% CI: 80.9% to 95.0%), 92.4% (95% CI: 86.0% to 96.5%), 89.4% (95% CI: 81.8% to 94.1%), and 92.2% (95% CI: 86.7% to 95.8%), respectively. The correlation coefficient equaled to 0.81 ( p < 0.001) between AccuIMR and wire-based IMR with the receiver-operating curve had area under the curve of 0.924 (95% CI: 0.878 to 0.956). Conclusions: AccuIMR is a novel pressure-wire free approach to assess coronary microvascular disease with great diagnostic performance, which can be a valid, efficient, and cost-reducing tool to provide an easier routine assessment of coronary microcirculation.